Detection and neutralisation of heparin by a fluorescent ruthenium compound - Szelke, Helga; Harenberg, Job; Krämer, Roland (Thrombosis and haemostasis, 2009)
Heparin and low-molecular-weight heparin (LMWH) are commonly monitored by determination of activated clotting times or chromogenic assays. Despite their wide use, these assays determine the biological activity and not the concentration of the anticoagulants. They may be inaccurate in some circumstances such as certain disease states. In addition, there is a significant interest in alternative tests for the point-of-care detection of heparin and LMWH. Their binding to small molecules for the detection in biological matrices is poorly explored. We describe here a new optical molecular probe for the detection of LMWH in serum samples. The polycationic ruthenium compound 1 is applicable to the quantification of heparin by monitoring 630 nm fluorescence. In addition, compound 1 is a rare example of a non-polymeric low molecular weight compound which neutralises the anticoagulant activity of heparin and LMWH in plasma samples. Limitation of the method is its low sensitivity currently being improved by structural modification of compound 1.